Nucleophilic H-Phosphites, H-Phosphinates, and H-Phosphine Oxides in Organic Reactions - Wang, Zhan-Yong; Guo, Qi; Xu, Shaohong; Wang, Kai-Kai (Synthesis, 2021)
P(O)–H compounds like H-phosphites, H-phosphinates, and H-phosphine oxides are widely used as nucleophiles. Herein, their reactions with unsaturated compounds, C–H activation, the Hirao reaction, P–C, P–S, P–O, P–N, and P–F couplings are thoroughly discussed and summarized. This review will focus on their reactions with alkenes, alkynes, enamides, propynoic acids, epoxide, arynes, arenes, quinones, isothiocyanates, diazo compounds, aldehydes, ketones, imines, pyridines, acid derivatives, carbocations, aryl halides, dibromoalkenes, disulfides, thiosulfates, sulfonyl chlorides, iodonium salts, amines, alcohols, and thiols.1 Introduction2 Addition to Alkenes/Alkynes3 Addition to Other Unsaturated Compounds4 Coupling with Carbocations5 Phosphorylation of Aryl C–H Bonds6 Hirao Reaction7 P–S, P–O, P–N, or P–F Coupling8 Conclusions
Keywords: mechanism; nucleophile; H-phosphites; H-phosphinates; H-phosphine oxides